2012
DOI: 10.1016/j.eurpsy.2010.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia: A five-year follow-up of patient outcome following psycho-education for caregivers

Abstract: This study, which is among the first to examine outcome over five years, supports the efficacy of psycho-education for caregivers in improving outcome for patients. Caregivers should be encouraged to take up psycho-education where it is available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
1
11
0
1
Order By: Relevance
“…However, the effect of the disease on the family is ignored. 2 - 5 In the study of Kavanagha, 19 which was carried out with the families of schizophrenic patients, he found that relapses increased in the patients of families whose expressed emotion level was high. Insufficient or incorrect knowledge of the family about the disease, its treatment and family attitudes affect their behaviours towards the patient and the symptoms of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the effect of the disease on the family is ignored. 2 - 5 In the study of Kavanagha, 19 which was carried out with the families of schizophrenic patients, he found that relapses increased in the patients of families whose expressed emotion level was high. Insufficient or incorrect knowledge of the family about the disease, its treatment and family attitudes affect their behaviours towards the patient and the symptoms of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of these negative feelings, their likelihood of depression may increase in the relatives, particularly the primary caregivers of the patient. 5 , 6 , 10 , 13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cassidy, Hill, and O'Callaghan (2001), found that the intervention successfully increased caregivers’ knowledge about schizophrenia, and more importantly, their ill relatives were less likely to be readmitted to the hospital during a 2-year follow up period. (See also McWilliams, Hill, Mannion, Fetherston, Kinella, & O'Callaghan, 2012). Together these findings are consistent with the view that increased psychosis literacy is associated with improved service use.…”
Section: The Current Researchmentioning
confidence: 98%